2023
DOI: 10.3390/en16031158
|View full text |Cite
|
Sign up to set email alerts
|

GaAs/Si Tandem Solar Cells with an Optically Transparent InAlAs/GaAs Strained Layer Superlattices Dislocation Filter Layer

Abstract: Epitaxial growth of III–V materials on Si is a promising approach for large-scale, relatively low-cost, and high-efficiency Si-based multi-junction solar cells. Several micron-thick III–V compositionally graded buffers are typically grown to reduce the high threading dislocation density that arises due to the lattice mismatch between III–V and Si. Here, we show that optically transparent n-In0.1Al0.9As/n-GaAs strained layer superlattice dislocation filter layers can be used to reduce the threading dislocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To mitigate severe Si carrier lifetime degradation during MBE growth, we introduced SiO 2 /SiN x impurity protection layers on the rear side of the Si. By also utilizing it as a rear surface passivation layer, we achieved a V oc of 0.539 V, marking a significant improvement over our previous result of 0.501 V . Furthermore, the Si subcell, filtered by a 1.65 eV Al 0.18 Ga 0.82 As buffer with increased transmittance, demonstrated a V oc of 0.548 V, which is higher than in the previous studies.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…To mitigate severe Si carrier lifetime degradation during MBE growth, we introduced SiO 2 /SiN x impurity protection layers on the rear side of the Si. By also utilizing it as a rear surface passivation layer, we achieved a V oc of 0.539 V, marking a significant improvement over our previous result of 0.501 V . Furthermore, the Si subcell, filtered by a 1.65 eV Al 0.18 Ga 0.82 As buffer with increased transmittance, demonstrated a V oc of 0.548 V, which is higher than in the previous studies.…”
Section: Discussioncontrasting
confidence: 45%
“…During LIV measurement, a metal aperture mask was employed to prevent any contributions from photogenerated carriers outside each cell area. In our previous work, we demonstrated that the photocurrent generated from an undefined p-type wafer directly influences the J sc of the Si subcell leading to overestimation of J sc . QE measurements were conducted using a Newport Quantx-300 with a 100 W xenon lamp source.…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate the impact of the TJ properties on the performance of the final solar cell under real working conditions, an Al 0.18 Ga 0.82 As top cell integrated with AlGaAs/ GaAs/AlGaAs TJs with either Si or Te as an n-type dopant in the n-TJ layer was grown on n-type GaAs substrates. This configuration was designed to demonstrate the effectiveness of our AlGaAs/GaAs/AlGaAs TJ for a 1.65 eV AlGaAs/1.12 eV Si tandem cell, 41 while disentangling the effects of dislocations arising from GaAs/Si heteroepitaxy. The design of the AlGaAs top cell integrated with 2 × 8% Te δ-doped TJs is illustrated in Figure 5a and characterized by scanning electron microscopy (SEM), providing a clear depiction of each layer within the structure (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…We have also conducted cross-sectional and plan-view TEM to investigate the evolution of TDs and MTs. Figure a,c shows the cross-sectional TEM images of Samples C and E. The measured specimen thickness was maintained at ∼100 nm to resolve the evolution of the various defects. , As highlighted by the red arrows in the cross-sectional TEM images, TDs were generated between GaSb and the GaP/Si substrate interface due to the high lattice mismatch, and these dislocations were greatly filtered by the DFL. The compressive strain forces most of the TDs to bend at the DFL interfaces rather than thread through them.…”
Section: Resultsmentioning
confidence: 99%